Harmonization of Parahyangan, Pawongan, and Pabelasan in the Pamalle Ritual: A Study of the Local Wisdom of the Sumbanese Community - Cordia, Grassiana Misseri; I Made Sutajaya; I Wayan Suja; Ida Bagus Made Astawa (International Journal of Educational and Life Sciences, 2024)
The aim of this article is to investigate how the philosophy of Tri Hita Karana (THK) is applied to the "Pindah Adat" tradition, also known as "Pamalle" in Sumba culture. THK actually originates from Balinese Hindu culture and emphasizes balance in three dimensions: balance in the relationship between humans and God (Parahyangan), balance in the relationship between people (Pawongan), and balance with the environment (Palemahan). In this article, the "Pamalle" tradition is explained as the custom of a woman moving to the man's family. This custom reflects the values of THK through spiritual, social, and environmental aspects. The traditional ritual has a spiritual aspect, which includes prayers and offerings to ancestors (Marapu) as a form of respect and request for blessings and protection. The Pamalle tradition teaches us that we can foster a sense of belonging and shared responsibility by involving all members of the community in decision-making. Ultimately, this will strengthen social ties and keep the community united. The Palemahan principle of Pamalle not only preserves the local ecosystem but also teaches the importance of a healthy relationship between humans and the environment. This tradition is a value system that continues to evolve and change over time, but its core remains the same, never changing. This study shows that the Pamalle tradition offers a new perspective on sustainable development based on local wisdom, applicable to everyone.